Electron–plasmon and electron–magnon scattering in ferromagnets from first principles by combining GW and GT self-energies - Dmitrii Nabok (Nature Portfolio, 2021)
Abstract This work combines two powerful self-energy techniques: the well-known GW method and a self-energy recently developed by us that describes renormalization effects caused by the scattering of electrons with magnons and Stoner excitations. This GT self-energy, which is fully k-dependent and contains infinitely many spin-flip ladder diagrams, was shown to have a profound impact on the electronic band structure of Fe, Co, and Ni. In the present work, we refine the method by combining GT with the GW self-energy. The resulting GWT spectral functions exhibit strong lifetime effects and emergent dispersion anomalies. They are in an overall better agreement with experimental spectra than those obtained with GW or GT alone, even showing partial improvements over local-spin-density approximation dynamical mean-field theory. The performed analysis provides a basis for applying the GWT technique to a wider class of magnetic materials.